ANALISIS PENGELOLAAN PIUTANG PENERIMAAN NEGARA BUKAN PAJAK DI POLITEKNIK NEGERI PONTIANAK - B51110091, Aryanie Sagita (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
Educatinal receivable which is classified in non-tax state revenue in Kementerian Pendidikan dan Kebudayaan is a disclaimer, a name given by Badan Pemeriksa Keuangan in 2011, because what has been recomended by Badan Pemeriksa Keuangan to make standard operational procedure (SOP) of educational receivable management in satate universities since 2009. In the year of 2012, Kementerian Pendidikan dan Kebudayaan issued SOP of educational receivable within Kementerian Pendidikan dan Kebudayaan and update it to receivable management guidline within Kementerian Pendidikan dan Kebudayaan in 2013. Politeknik Negeri Pontianak is an institution under Kementerian Pendidikan dan Kebudayaan and its educational receivable had increased in the last three years (2012-2014).The research aimed to find out whether receivable management implementation of non-tax state revenue was in line with Technical Bulletin Number 6 in the year of 2008 about Receivale Accounting and Eeceivable Management Guideline within Kementerian Pendidikan dan Kebudayaan, and to know problems in managing receivable of on-tax state revenue of Politeknik Negeri Pontianak. The methodology of the research was descriptive by using qualitative analysis approach. Questionnaire, observation, documentation, and library research were used as data collecting technique.The research findings showed that educational receivable management of non-tax state revenue of  Politeknik Negeri Pontianak did not run well according to Technical Bulletin Number 6 in the year of 2008 about Receivable Accounting and Receivable Management Guideline within Kementerian Pendidikan dan Kebudayaan. Besides, it was found that some problem occurred during managing the receivable. They were lack of knowledge of staff who managed the receivable, lack of internal control from the head, absence of standard operational procedure of internal educational receivable management, and incompatibility of bookkeeping between theory and practice.  Keywords : Management, Educational Receivable of Non-Tax State   Revenue